2020
DOI: 10.1016/j.ajodo.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional facial capture using a custom-built photogrammetry setup: Design, performance, and cost

Abstract: Introduction: Although stereo-photogrammetry is increasingly popular for scanning faces three-dimensionally, commercial solutions remain quite expensive, limiting their accessibility. We propose a more affordable, custom-built photogrammetry setup (SF3D), and evaluate its variability within-and between-systems. Methods: 29 subjects and a mannequin head were imaged three times using SF3D and a commercially available system (3dMDFace). Next, an anthropometric mask was mapped visco-elastically onto the reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…The present study found agreement between 2D photogrammetry and other methods, which suggests that 2D measurements can be safely used in images collected with accurate technique and attention. Farkas et al [29] and Wellens et al [30] reported that, by the distortions in photogrammetry, the difference between direct anthropometry and 2D photogrammetry may be caused. It seems crucial to make the calibration in the same plane as the measuring points in 2D measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found agreement between 2D photogrammetry and other methods, which suggests that 2D measurements can be safely used in images collected with accurate technique and attention. Farkas et al [29] and Wellens et al [30] reported that, by the distortions in photogrammetry, the difference between direct anthropometry and 2D photogrammetry may be caused. It seems crucial to make the calibration in the same plane as the measuring points in 2D measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Other depth-acquisition techniques include: depth from defocus, depth from focus, pulse ranging, time-of-flight, phase-based, or continuous wave ranging methods [ 1 ], in addition to confocal, active wave sampling [ 2 ]. Types of 3D scanners relevant for orthodontic applications include (this list is by no means exhaustive): for face scanning: Vectra, 3DiD, 3dMD [ 3 ], EinScan Pro and Planmeca [ 4 ], Konica Minolta 910, and Polhemus [ 5 ]; desktop scanners for scanning plaster dental models: Konica Minolta VI-9i and Imetric laser scanner [ 6 ]; intraoral scanners: Trios, iTero Element, Dental Wings, Panda 2, Medit i500, Planmeca, and Aoralscan [ 7 ]. …”
Section: Introductionmentioning
confidence: 99%
“…for face scanning: Vectra, 3DiD, 3dMD [ 3 ], EinScan Pro and Planmeca [ 4 ], Konica Minolta 910, and Polhemus [ 5 ];…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations